Light-driven Pickering interfacial catalysis for the oxidation of alkenes at near-room temperature. Issue 4 (2nd February 2023) - Feng, Yaoyao; Dechezelles, Jean-François; D'Acremont, Quentin; Courtade, Emmanuel; De Waele, Vincent; Pera-Titus, Marc; Nardello-Rataj, Véronique
Abstract : The synergistic effect of plasmonic Au and catalytic [C12 ]3 [PW12 O40 ] NPs in a PIC system for light-driven alkene oxidation at T room . Abstract : In this study, we have developed an emulsion system combining plasmonic Au-loaded amphiphilic silica nanoparticles (Au/SiO2 –C3 ) and tri(dodecyltrimethylammonium) phosphotungstate ([C12 ]3 [PW12 O40 ]) nanoparticles acting as an on-site photoassisted heater/activator and a catalyst, respectively, at the water/oil interface. The system exhibits a 5-fold increase of activity compared to the thermal reaction for the near-room temperature oxidation of alkenes with H2 O2 . The nanoparticles show excellent recyclability and structural stability. This study opens an avenue to design multiphase photoreactors for oxidation reactions at mild temperature, with a potential energy saving of 74% compared to that of thermally heated reactors at isoconversion.